2021
DOI: 10.1002/ejp.1863
|View full text |Cite
|
Sign up to set email alerts
|

Auditory change‐related cortical response is associated with hypervigilance to pain in healthy volunteers

Abstract: Background: Patients with chronic pain exhibit hypervigilance (heightened responsiveness to stimuli) to innocuous auditory stimuli as well as noxious stimuli."Generalized hypervigilance" suggests that individuals who show heightened responsiveness to one sensory system also show hypervigilance to other modalities. However, research exploring the existence of generalized hypervigilance in healthy subjects is limited.Methods: We investigated whether hypervigilance to pain is associated with auditory stimuli in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Carrillo-de-la-Pena and colleagues ( Carrillo-de-la-Pena et al, 2006 ) examined auditory ERPs to a range of tone intensities and reported greater N1-P2 amplitudes and shorter latencies to very loud tones (105 dB) in FM participants compared to the CNT group, but did not replicate this finding in a follow-up study ( Samartin-Veiga et al, 2020 ). Converging support for cross-sensory hypervigilance has been provided by a recent study in healthy participants ( Otsuru et al, 2022 ), which reported a significant association between auditory change-related ERPs and attention and sensitivity to pain. This aligns with deficient habituation of the auditory N100 in FM participants reported in one study ( Choi et al, 2016 ), but another one failed to show this effect ( Montoya et al, 2006 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Carrillo-de-la-Pena and colleagues ( Carrillo-de-la-Pena et al, 2006 ) examined auditory ERPs to a range of tone intensities and reported greater N1-P2 amplitudes and shorter latencies to very loud tones (105 dB) in FM participants compared to the CNT group, but did not replicate this finding in a follow-up study ( Samartin-Veiga et al, 2020 ). Converging support for cross-sensory hypervigilance has been provided by a recent study in healthy participants ( Otsuru et al, 2022 ), which reported a significant association between auditory change-related ERPs and attention and sensitivity to pain. This aligns with deficient habituation of the auditory N100 in FM participants reported in one study ( Choi et al, 2016 ), but another one failed to show this effect ( Montoya et al, 2006 ).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, the supporting evidence for generalized hypervigilance in other modalities has been mixed. While some researchers report augmented early ERPs ( Carrillo-de-la-Pena et al, 2006 , Otsuru et al, 2022 ) and deficient habituation of the N100 to auditory stimuli ( Choi et al, 2016 ), others have failed to find greater FM sensitivity to tones ( Lorenz, 1998 , Samartin-Veiga et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%